2018
DOI: 10.1073/pnas.1719871115
|View full text |Cite
|
Sign up to set email alerts
|

The glycerol backbone of phospholipids derives from noncarbohydrate precursors in starved lung cancer cells

Abstract: SignificancePhosphoenolpyruvate carboxykinase (PEPCK) has a unique position in cell metabolism by allowing the flexible use of nutrients for anabolic biosynthetic reactions. PEPCK activity has just recently been described in cancer cells. It has been shown to promote cancer cell survival under nutrient deprivation, a typical feature in solid cancers, as well as cancer growth. To decipher the metabolic downstream pathways of PEPCK is critical for a better understanding of cancer cell adaptive responses under lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 50 publications
6
59
0
Order By: Relevance
“…Cellular PEP levels are also maintained by the PEPCK-dependent cataplerosis of TCA cycle carbons that contribute to the synthesis of glycolytic intermediates (Hyrossova et al, unpublished), serine/glycine [19] and triglycerides [20,21]. In most tumor models, and specifically in the cellular models utilized in this work, the mitochondrial isoform of PEPCK (PEPCK-M) plays this key role as it is the only isoform of PEPCK expressed [22].…”
Section: Glycolytic and Cataplerotic Fluxes Towards Pep Cooperate To mentioning
confidence: 99%
“…Cellular PEP levels are also maintained by the PEPCK-dependent cataplerosis of TCA cycle carbons that contribute to the synthesis of glycolytic intermediates (Hyrossova et al, unpublished), serine/glycine [19] and triglycerides [20,21]. In most tumor models, and specifically in the cellular models utilized in this work, the mitochondrial isoform of PEPCK (PEPCK-M) plays this key role as it is the only isoform of PEPCK expressed [22].…”
Section: Glycolytic and Cataplerotic Fluxes Towards Pep Cooperate To mentioning
confidence: 99%
“…For the glycerophospholipid metabolism term, phosphoenolpyruvate carboxykinase (PEPCK) has been shown to promote cancer cell survival under conditions of nutrient deprivation, a typical feature in solid cancers, as well as cancer growth (Méndez-Lucas et al, 2014;Leithner et al, 2015;Montal et al, 2015;Vincent et al, 2015). Recently, Leithner et al (2018) further showed that mitochondrial PEPCK (PEPCK-M) mediates the synthesis of glycerol phosphate from noncarbohydrate precursors, and that PEPCKM is needed to maintain the levels of glycerophospholipids, major constituents of biomembranes, in starved lung cancer cells.…”
Section: Enrichment Analysis Of Pathways and Biological Processesmentioning
confidence: 99%
“…Partially, this occurs by circumventing the glycolytic pathway and instead using some steps of gluconeogenesis from noncarbohydrate precursors to overcome metabolic stress (for review, see [8]). The key enzyme mediating gluconeogenesis, phosphoenolpyruvate carboxykinase (PEPCK), has been recently discovered to replenish glycolytic pools in cancer cells of different origins and thus to mediate abbreviated gluconeogenesis [9][10][11][12][13]. In numerous studies, PEPCK was shown to enhance tumor cell metabolic flexibility under glucose deprivation [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are two isoforms of PEPCK: the cytoplasmic isoform PCK1, and PCK2, the mitochondrial isoform [16,17]. In tumor cells of various origins, PCK1 or PCK2 have been found to mediate abbreviated gluconeogenesis, especially under conditions of glucose deprivation, thus contributing to anabolic metabolism [9,[11][12][13]. The downstream metabolic pathways fueled by PCK1 or PCK2 in cancer cells include the biosynthesis of the phospholipid glycerol backbone [13], serine [11], or ribose [12,18].…”
Section: Introductionmentioning
confidence: 99%